Remote detection of placer deposits and iron-bearing minerals using the infrared spectrum for the identification of environmental monitoring sites in Benguet catchment - Isidro, Celso M.
This study aims to investigate, using infrared spectrum the remote detection of placer deposits and their zone of mineral concentrations to identify environmental monitoring sites. The Modified Normalized Difference Water Index (MNDWI) completely separated placer deposits from river networks and lakes. It was observed that water areas highly absorbed shortwave infrared light from 1.57 um to 1.65 um of Landsat-8 OLI sensor, which resulted in positive MNDW index values. Whereas placer deposits reflected shortwave infrared light, and negative MNDW index was generated over these areas. In contrast, the application of Ferrous Minerals Ratio (FMR) index presented that iron-bearing minerals were separable from other placer materials due to their higher reflectance at shortwave infrared region. During rainy season, mudflow induced by rain covered placer materials near the discharge outlets whereas turbid water washed-out placer materials at higher elevations. Turbid water and mudflow resulted in spectral signatures that have low reflectance at shortwave infrared, but high reflectance at near-infrared region compared. This phenomenon reduced detected placer deposits area coverage of 2 km2 and 3.7 km2 for 2014 and 2015, respectively. An inverse linear relationship was generated between MNDWI and surface temperature, with an R2 value of 70 %. In addition, washed-out iron-bearing minerals were continuously replenished every dry season. They were detected as additional area coverage during the 1st and 2nd quarters which ranges from 0.1 km2 to 1.7 km2.